2001
DOI: 10.3758/bf03192817
|View full text |Cite
|
Sign up to set email alerts
|

Habituation may contribute to within-session decreases in responding under high-rate schedules of reinforcement

Abstract: Two experiments tested the hypothesis that habituation contributes to within-session decreases in responding. In Experiment 1, rats' leverpressing was reinforced under a fixed ratio (FR) 4 schedule throughout the baseline sessions. During the dishabituation sessions, the first 21 min and the last 21 min were FR 4; dishabituating events occurred during the middle 3 min. The dishabituating events altered the manner of reinforcer delivery in four different ways. Response rates increased after all dishabituating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 43 publications
4
36
0
Order By: Relevance
“…Within-session changes in responding under constant conditions have been reported widely for operant procedures (e.g., Aoyama & McSweeney, 2001;McSweeney & Roll, 1993). For the rabbit NM preparation, however, within-session decreases under constant reinforcement have been observed only occasionally (Tait, Kehoe, & Gormezano, 1983), and certainly not commonly (e.g., Macrae & Kehoe, 1999;Napier et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Within-session changes in responding under constant conditions have been reported widely for operant procedures (e.g., Aoyama & McSweeney, 2001;McSweeney & Roll, 1993). For the rabbit NM preparation, however, within-session decreases under constant reinforcement have been observed only occasionally (Tait, Kehoe, & Gormezano, 1983), and certainly not commonly (e.g., Macrae & Kehoe, 1999;Napier et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 presents an example of dishabituation taken from Aoyama and McSweeney (2001b;see also McSweeney & Roll, 1998). During baseline, rats pressed a lever for a reinforcer of one food pellet delivered according to a fixed-ratio (FR) 4 schedule in a 45-min session.…”
Section: Separating Satiation and Habituationmentioning
confidence: 99%
“…This parameter represents the cumulative number of reinforcer deliveries that will reduce the response rate to zero. Although it has been repeatedly demonstrated that Equation 1 can describe responding for primary reinforcers (e.g., Aoyama, 2007; 2012; Aoyama & McSweeney, 2001), Equation 1 has never been applied to responding for secondary reinforcers. Thus, in this study, Equation 1 was applied to the within-session responding for the cue previously associated with saccharin.…”
Section: Introductionmentioning
confidence: 99%